Invadosomes as “shape-shifters” of cellular maturation: insights from megakaryocytes - Frédérique Gaits-Iacovoni (Frontiers in Cell and Developmental Biology)
Invadosomes are a family of subcellular actin-based structures essential for cell–extracellular matrix (ECM) interaction and remodeling. In non-invasive cells, they are referred to as podosomes, which enable adhesion, migration, and ECM remodeling via secretion of metalloproteinases or mechano-traction. In invasive tumoral cells, these structures are called invadopodia due to their function. Despite structural similarity, podosomes appear as highly regular dots in 2D and do not always exhibit ECM-degradative abilities; hence, the term “degradative dot-podosomes” is used in this paper. Invadopodia are consistently degradative, fewer in number, slightly larger, deeper, less regular-shaped, and longer-lived. In tumor cells, collagen I induces the formation of linear invadosomes, which promote invasion by degrading collagen through the action of MT1–MMP (membrane type 1–matrix metalloproteinase) and the adaptor protein Tks5 (tyrosine kinase substrate 5). Interestingly, linear invadosomes also appear in non-tumor cells, such as megakaryocytes (MKs)—the platelet precursors—which display podosomes that closely resemble invadopodia. As MKs mature, Tks5 expression decreases, and dot-podosomes align along collagen I fibers, fusing into linear podosomes that remodel the ECM through mechanical traction but have lost their degradative ability. The GTPase Cdc42, crucial for invadosome formation, remains highly active in the MK internal demarcation membrane system (DMS) but is downregulated in linear podosomes. These observations suggest that Tks5, considered a marker of metastatic potential, also plays roles in normal physiology. Thus, linear podosomes with mechanotransductive properties may exist in a broader range of non-transformed cells. This mini-review focuses on the linear subfamily of invadosomes, highlighting their structure and function in MKs, a model in which invadosomes remain underexplored.